Pycnodysostosis: Clinicoradiographic report of a rare case - Mayur D Dhameliya; Ajit D Dinkar; Manisha Khorate; Sapna S Raut Dessai (Contemporary Clinical Dentistry, 2017)
Pycnodysostosis is an uncommon autosomal recessive sclerosing bone disorder which is characterized by short stature and generalized diffuse osteosclerosis. Patients usually have a large head with separated sutures, open fontanels, aplasia of frontal sinuses, obtuse mandibular gonial angle, and acroosteolysis of the distal phalanges. This case report showed a 25-year-old female with features pathognomonic of pycnodysostosis. The emphasis is mainly on the early diagnosis as it has an important role in the general health of such patients and prevention of complications.